Screening effects of HCN channel blockers on sleep/wake behavior in zebrafish - Doldur-Balli, Fusun; Smieszek, Sandra P.; Keenan, Brendan T.; Zimmerman, Amber J.; Veatch, Olivia J.; Polymeropoulos, Christos M.; Birznieks, Gunther; Polymeropoulos, Mihael H. (Frontiers in Neuroscience, 2024)
Hyperpolarization-activated cyclic nucleotide-gated (HCN) ion channels generate electrical rhythmicity in various tissues although primarily heart, retina and brain. The HCN channel blocker compound, Ivabradine (Corlanor), is approved by the US Food and Drug Administration (FDA) as a medication to lower heart rate by blocking hyperpolarization activated inward current in the sinoatrial node. In addition, a growing body of evidence suggests a role for HCN channels in regulation of sleep/wake behavior. Zebrafish larvae are ideal model organisms for high throughput drug screening, drug repurposing and behavioral phenotyping studies. We leveraged this model system to investigate effects of three HCN channel blockers (Ivabradine, Zatebradine Hydrochloride and ZD7288) at multiple doses on sleep/wake behavior in wild type zebrafish. Results of interest included shorter latency to daytime sleep at 0.1 μM dose of Ivabradine (ANOVA, p:0.02), moderate reduction in average activity at 30 μM dose of Zatebradine Hydrochloride (ANOVA, p:0.024) in daytime, and increased nighttime sleep at 4.5 μM dose of ZD7288 (ANOVA, p:0.036). Taken together, shorter latency to daytime sleep, decrease in daytime activity and increased nighttime sleep indicate that different HCN channel antagonists affected different parameters of sleep and activity.